Management of patients with heart failure in clinical practice: differences between men and women. Issue 3 (17th June 2007) - Lenzen, M J; Rosengren, A; op Reimer, W J M Scholte; Follath, F; Boersma, E; Simoons, M L; Cleland, J G F; Komajda, M
Abstract : Objectives: This study evaluated gender differences in clinical characteristics, treatment and outcome among patients with heart failure, and to what extent these differences are due to age and differences in left ventricular (LV) function. Although gender differences are observed among heart failure patients, few studies have been adequately powered to investigate these differences. Methods: A total of 8914 (out of 10 701) patients (47% women) from the Euro Heart Survey on Heart Failure with confirmed diagnosis of heart failure were included in the analyses. Results: Women were older (74.7 vs 68.3 years, p<0.001), and less often had evidence of coronary artery disease (56% vs 66%, age-adjusted odds ratio (OR) 0.62; 95% CI 0.57 to 0.68). Women were more likely to have hypertension, diabetes, or valvular heart disease. Fewer women had an investigation of LV function (59% vs 74%, age-adjusted OR 0.67; 95% CI 0.61 to 0.74), and, among those investigated, fewer had moderate/severe left ventricular systolic dysfunction (44% vs 71%, age-adjusted OR 0.35; 95% CI 0.32 to 0.39). Drugs with a documented impact on survival, that is ACE-inhibitors and β-blockers, were given less often to women, even in the adjusted analysis (OR 0.72; 95% CI 0.61 to 0.86 and OR 0.76; 95% CI 0.65 to 0.89, respectively). 12-week mortality was similar for men and women. Conclusions: Fewer women had an assessment of LV function, but, when investigated, women had better ventricular function. Women were less often treated with evidence-based drugs, even after adjustment for age and important clinical characteristics. Clinicians need to be aware of deficiencies in the treatment of women with heart failure and measures should be taken to rectify them.